Management of Education Funding in Improving the Quality of Education at Junior High School - Hotmaida Sidabutar; Sukarman Purba; Restu Restu; Eka Daryanto; Taufiq Ramadhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
As well as knowing and analyzing the form of management accountability at SMP Santa Lucia Sei Rotan in managing the school's income and expenditure budget. This type of research uses descriptive qualitative methods and research methods use library research. The results of the study show that the budgeting process carried out by the management of SMP Santa Lucia Sei Rotan has not been able to optimize properly to improve the quality of existing human resources, and the process of channeling the budget has not touched the programs implemented to create students who have talents and qualified abilities in accordance with the vision, mission and school goals